Dense vs. Sparse Retrieval Throughput in Phi-3-Mini Long-Context Generation - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 12 peer-reviewed papers addressing the following research question: What is the throughput impact of dense versus sparse retrieval on Phi-3-mini's response generation time when evaluated on long-context benchmarks, measured in tokens per second. 12 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.7/10. This report is a machine-generate
Machine-generated literature synthesis.